Effective Communication and Financial Management in Secondary Schools in Meru County, Kenya - Mungai, Sarah Njeri (Journal of Education and Practice, 2025)
Purpose: To assess the influence of effective communication on financial management in secondary schools in Meru County, Kenya. Methodology: The study adopted descriptive research design to collect data from 389 secondary schools in Meru County. The respondents were 389 principals and 389 senior teachers. Simple random sampling method was used after the sample size of the schools was obtained by determining 30% of the population. This resulted to 117 principals and 117 senior teachers in 117 secondary schools. The study collected quantitative data through use of questionnaires. The pilot testing was done in Isiolo county where 10% of the sample size was used to determine the pilot population. Reliability was tested through the use of Cronbach alpha while content, criterion and construct validities were determined as well. Descriptive statistics like frequencies, percentages and mean were provided whereas Pearson correlation was used to test the hypothesis of the study. The presentation of the results was done through Tables and explicit explanations was provided. Results: The results revealed that 181(95%) respondents on mean of 4.68 and 179(84%) respondents on mean of 4.42 that decisions made were stronger and improved productivity among staff due to effective communication respectively. However, 158(74%) respondents failed to ascertain that the school did not provide updated information to stakeholders. The Pearson correlation coefficient r=0.572** at α < 0.000 and 99% significance level. This meant that there was a positive influence since the Pearson correlation value in both cases were less than 1 and significance level less than 0.05, hence rejected the null hypothesis by concluding that effective communication had significant influence on financial management in secondary schools. Unique contribution to theory, policy and practice: There were weaknesses in the manner in which principals were communicating information to stakeholders, largely because of capabilities and inefficacies in some cases. Further, there was less communication to staff on various matters as it ought to be. This left room for staff to make false conclusions and spread the same to others as ostensibly coming from the management. It is the recommendation of the study that the principals should put measures to ensure systems are duly updated to foster efficiency. Further the management should come up with schedules of meetings on time so as to allocate effective timelines for communication purposes.